Modeling the protective effect of previous compulsory smallpox vaccination against human monkeypox infection: from hypothesis to a worst-case scenario. (November 2022) - Spath, Tibor; Brunner-Ziegler, Sophie; Stamm, Tanja; Thalhammer, Florian; Kundi, Michael; Purkhauser, Kim; Handisurya, Alessandra
Highlights: A model of the age-dependent smallpox vaccine-induced protection against monkeypox (MPX) is presented. The population's immunity alone may not suffice to contain MPX dissemination. The presented model is easily applicable to other populations worldwide. Coordinated public health measures to stop the spread of MPX are urgently needed. Abstract: Objectives: Human monkeypox (MPX) cases are escalating worldwide. Smallpox vaccination, which was compulsory in Austria until 1981, was reported to confer 85% cross-protection against MPX. Methods: To assess the impact of smallpox vaccine-induced protection, the age-dependent vaccine-induced immunity against human MPX and the probability of infection according to age in the general population of Vienna, Austria, were determined using a modified susceptible-infected-removed model. Results: Within the population born before 1981, the average vaccine-induced protective effect was calculated at 50.4%, whereas in the population born thereafter, protection was lacking. The overall probability of infection after exposure to an infected patient was calculated at 73.8%, which exceeds the threshold value of 46.9% for an index patient to infect at least one other person (R ≥1.0). Conclusion: Our model shows that if no additional interventions are taken, the collective immunization status of the population alone will not suffice to contain human MPX. Although the majority of cases have occurred in a subpopulation, given the steadily increasing incidence, dissemination into the general population remains possible, as observed before with HIV. Our model emphasizes the need for adequate containment measures and may aid in specific risk assessment because it can easily be adapted to other populations and cohorts worldwide.